Self Awareness With Wisdom Based Thinking Skills Approach In PAI Learning - Danial, Muhammad; Sijabat, Jenro Pandu (Early Publishing, 2025)
Islamic religious education learning should ideally optimize the potential of the mind that Allah SWT has given. This potential of the mind is an important potential in the formation of human morals. The ability to reflect on oneself is part of the nobility of human reason. In childhood and adolescence, the ability to reflect on oneself to understand oneself and others is still in the early stages of its development. According to a survey fromy from the Indonesian National Adolescent Mental Health Survey (I-NAMHS) conducted in 2021, out of three Indonesian teenagers, one of them experiences mental health disorders. Around 43.8% of them do not receive the counseling assistance they need, so they are required to solve the mental disorders they experience independently. The above conditions require attention from education stakeholders, especially Islamic Religious Education teachers who are concerned with the formation of student character. Islamic religious education learning should ideally be able to develop rational thinking awareness in the form of dialectical and reflective thinking skills as a way to foster students' mental health in the form of self-awareness. The research method used is a literature review, namely conducting content analysis to find conclusions from the data and references collected. The purpose of this study is to find a theory that can be implemented to increase self-awareness in Islamic Religious Education learning. The results of this study found that the right stimulation to develop self-awareness includes using the wisdom-based thinking skills approach, which is a learning approach that solves problems by reflecting, dialoguing, and dialectic. Dialogue and dialectic skills can be trained in the problem-based learning model with the six thinking hats technique by Edward de Bono.